Answer:
The numbers are
and
![18(2)/(3)](https://img.qammunity.org/2021/formulas/mathematics/college/2m0zkx4yntssp3z9nk10aafvkc6tysxqic.png)
Explanation:
Let x and y be the numbers
According to the statement, "The sum of two number is 18.", first equation will be:
![x+y = 18\ \ \ \ Eqn\ 1](https://img.qammunity.org/2021/formulas/mathematics/high-school/e9j7trltu8ndkvfcapom5km1g34e1c9tkc.png)
And according to "The sum of two number is 18. 5 times the first number subtracted from 4/7bof the second number is 14." Second equation will be:
![(4)/(7)y-5x = 14](https://img.qammunity.org/2021/formulas/mathematics/high-school/25lts24k7ekk765n9mqmqmf4wso199ullw.png)
Multiplying whole equation by 7
![7*(4)/(7)y-7*5x = 7*14\\4y-35x=98\\-35x+4y = 98\ \ \ \ Eqn\ 2](https://img.qammunity.org/2021/formulas/mathematics/high-school/mv3vgeg06jb86k9fbf75vxbdem57euww0d.png)
From equation 1
![x+y = 18\\y = 18-x](https://img.qammunity.org/2021/formulas/mathematics/high-school/ailx1e3e11cgwzu19q3n6vcz5uln63oalm.png)
Putting this in second equation
![-35x+4(18-x) = 98\\-35x+72-4x= 98\\-39x = 98-72\\-39x = 26\\(-39x)/(-39) = (26)/(-39)\\x = -(2)/(3)](https://img.qammunity.org/2021/formulas/mathematics/high-school/tkddfm5xxyyt9sgyvj762ua9wc4y22e35z.png)
Putting x = -2/3 in equation 1
![-(2)/(3)+y = 18\\y = 18+(2)/(3)\\y = 18(2)/(3)](https://img.qammunity.org/2021/formulas/mathematics/high-school/2uroc66gnzamklu395iuf8xuzq0ge43zoh.png)
Hence, the numbers are
and
![18(2)/(3)](https://img.qammunity.org/2021/formulas/mathematics/college/2m0zkx4yntssp3z9nk10aafvkc6tysxqic.png)